Day 2 Tue, September 27, 2016 2016
DOI: 10.2118/181503-ms
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dots Fluorescent Tracers for Production and Well Monitoring

Abstract: Tracer technology is a very efficient diagnostic tool for the oil and gas industry to obtain valuable information about reservoirs. The interpretation of tracers that have traversed the reservoir reveals reservoir characteristics such as inter-well connections, heterogeneities, and water movements that can be used to improve hydrocarbon recovery efforts. Commonly used tracers are radioactive elements and stable isotopes, chemicals, such as fluorescent dyes, and inorganic ions. Novel carbon quantum dots (CQDs)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…These wavelengths are common for carbonaceous quantum dots with oxygenated and nitrogenated functional groups. Mugressan et al showed how the presence of nitrogen in N-doped CQDs generates a blue shift in the fluorescence wavelength. Hence, it is possible to change the color, or the fluorescence wavelength, by changing the chemical composition or introducing dopants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These wavelengths are common for carbonaceous quantum dots with oxygenated and nitrogenated functional groups. Mugressan et al showed how the presence of nitrogen in N-doped CQDs generates a blue shift in the fluorescence wavelength. Hence, it is possible to change the color, or the fluorescence wavelength, by changing the chemical composition or introducing dopants.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of these results, the authors concluded that these types of nanoparticles have a tracer behavior and can be used for understanding interwell fluid dynamics. Murugesan et al 12 reported on CQDs synthesized using an electrochemical reaction. These CQDs showed different colors under UV irradiation, depending on the nitrogen content in their structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Core flow experiments showed that the recovery of CQDs in 1 wt % NaCl solution was 76% in cores with low permeability. CQDs thus provide a new alternative for tracers for monitoring reservoir conductions [166].…”
Section: Tracermentioning
confidence: 99%
“…Carbonaceous nanomaterials are emerging as a sustainable alternative to their metal oxide counterparts. Carbon or graphene quantum dots (QDs), in particular, possess a unique set of attributes such as nanoscale size, low toxicity, high stability under harsh reservoir conditions, and tunable physicochemical properties, which make them ideal additives for these applications. Furthermore, the quantum confinement effect due to the graphitic backbone of QDs endows them with fluorescent properties and the potential to be utilized as tracers for production and well monitoring and reservoir characterization . Given their small diameters (<10 nm) compared to the typical pore and throat sizes, , QDs are unlikely to cause any clogging issues if their retention by the rock is minimized.…”
Section: Introductionmentioning
confidence: 99%